2010
DOI: 10.3109/0142159x.2010.485653
|View full text |Cite
|
Sign up to set email alerts
|

Using the cumulative deviation method for cross-institutional benchmarking in the Berlin progress test

Abstract: The Berlin Progress Test has grown to a cooperation of 13 universities. Recently, comparisons between the participating schools became an area of high interest. Muijtjens et al. [Muijtjens AM, Schuwirth LWT, Cohen-Schotanus J, Thoben AJNM, van der Vleuten CPM. 2008a. Benchmarking by cross-institutional comparison of student achievement in a progress test. Med Educ 41(1):82-88; Muijtjens AM, Schuwirth LWT, Cohen-Schotanus J, van der Vleuten CPM. 2008b. Differences in knowledge development exposed by multi-curri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 10 publications
2
20
1
Order By: Relevance
“…The total variance explained by the three dimensions of empathy was 37.4% which is similar to the values reported in the literature [17]. Confirmatory Factor Analysis (CFA) revealed that the model with "no correlated errors" (Fit Model A) displayed poor fit index values, based on the χ2/df ratio, the Comparative Fit Index (CFI) and Root Mean Square Error of Aproximation (RMSEA) [27,28].…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…The total variance explained by the three dimensions of empathy was 37.4% which is similar to the values reported in the literature [17]. Confirmatory Factor Analysis (CFA) revealed that the model with "no correlated errors" (Fit Model A) displayed poor fit index values, based on the χ2/df ratio, the Comparative Fit Index (CFI) and Root Mean Square Error of Aproximation (RMSEA) [27,28].…”
Section: Resultssupporting
confidence: 78%
“…Recent cross-sectional studies in Japan and Korea found the highest values for measures of empathy, by year of medical school, in senior students [15,16]. A cross-sectional study in Iran did not find variations in empathy [17]. The effect of undergraduate medical training on the development of medical students' empathy remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to emotional empathy score, this may be also associated with the training in medical education or experience during the clinical years. Similar studies have found contradicting findings in this regard; studies in Japan and Korea found the highest values for measures of empathy, by year of medical school, among senior medical students [7,36] while another study in Iran did not find variations in empathy [37]. This difference might be attributed to the instruments used; since, in the Korean study they measured clinical empathy than general empathy.…”
Section: Discussionmentioning
confidence: 87%
“…Empathy is related to understanding patients feelings and, not surprisingly, patients who feel understood are more likely to fully explain their symptoms and to engage in the patient-physician relationship [8]. The multiple definitions of empathy in the medical education literature [9] characterize empathy as a mix of cognitive - understanding patient emotions and communicating the understanding back to the patients - and affective dimensions - emotional responses to patient feelings [10], [11]. The cognitive dimension is amenable to training and therefore an important mission of medical schools is that of caring for and enhancing the empathy of medical students [12][15].…”
Section: Introductionmentioning
confidence: 99%